Gut microbial predictors of first-line immunotherapy efficacy in advanced NSCLC patients - Anna Grenda; Ewelina Iwan; Barbara Kuźnar-Kamińska; Arkadiusz Bomba; Katarzyna Bielińska; Paweł Krawczyk; Izabela Chmielewska; Małgorzata Frąk; Michał Szczyrek; Anna Rolska-Kopińska; Tomasz Jankowski; Robert Kieszko; et al. (Scientific Reports)
Abstract The composition of the gut microbiome of patients with advanced non-small cell lung cancer is currently considered a factor influencing the effectiveness of treatment with immune checkpoint inhibitors. We aimed to evaluate the baseline gut microbiome composition in patients before receiving first-line immunotherapy alone or combined with chemoimmunotherapy. We performed 16S rRNA sequencing based on hypervariable regions. Stool samples were collected from 52 patients with advanced NSCLC treated with immunotherapy or chemoimmunotherapy before treatment. We found that the Ruminococcaceae family, species Alistipes sp. genus Eubacterium ventriosum group and genus Marvinbryantia may be intestinal, microbiological predictors of response to treatment. Genus Akkermansia and species from the [Clostridum] leptum group predicted the length of PFS (progression-free survival). Longer OS (overall survival) is associated with bacteria from the Ruminococcaceae family genera [ Eubacterium ] ventriosum group, Marvinbryantia, Colidextribacter and species [Clostridum] leptum. Bacteria that have an adverse effect (shortening of PFS or OS) on the response to treatment using immune checkpoint inhibitors are Rothia genus, Streptococus salivarius, Streptococus, Family XIII AD3011 group and Family XIII AD3011 group, s. uncultured bacterium. The composition of intestinal flora can be a predictive factor for immunotherapy in NSCLC patients. Specific bacteria can be positively or negatively associated with response to treatment, progression-free survival, and overall survival. They can be potentially used as predictive markers in NSCLC patients treated with immunotherapy.